2020
DOI: 10.1055/a-1044-2321
|View full text |Cite
|
Sign up to set email alerts
|

Similar Effects of Acute Resistance Exercise on Carotid Stiffness in Males and Females

Abstract: Sex differences exist in vascular responses to blood pressure perturbations, such as resistance exercise. Increases in aortic stiffness following acute resistance exercise appear different between sexes, with attenuated increases in females vs. males. Whether sex differences exist in carotid stiffness, following resistance exercise is unknown. This study sought to examine sex differences in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Meanwhile, for RT, which is the most commonly studied type of exercise among middle-aged women, there are two studies [ 41 , 45 ] that reported positive effects on arterial stiffness in middle-aged women (about 10.97% improvement), while five others do not [ 20 , 38 , 39 , 46 , 48 ]. The lack of changes following RT in this age group could be due to multifactorial reasons, (i) exercise intensity, (ii) mode of contraction, and (iii) muscle group tested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, for RT, which is the most commonly studied type of exercise among middle-aged women, there are two studies [ 41 , 45 ] that reported positive effects on arterial stiffness in middle-aged women (about 10.97% improvement), while five others do not [ 20 , 38 , 39 , 46 , 48 ]. The lack of changes following RT in this age group could be due to multifactorial reasons, (i) exercise intensity, (ii) mode of contraction, and (iii) muscle group tested.…”
Section: Resultsmentioning
confidence: 99%
“…Although low–moderate intensity RT based on RM and body weight showed a positive effect on arterial stiffness [ 41 , 45 ], several other studies reported that light-intensity RT based on RM has either a detrimental effect or no effect on vascular health [ 38 , 46 , 48 ], while high-intensity RT with maximal isokinetic knee extension/flexion also has a negative effect on arterial stiffness [ 39 ] in middle-aged women. In addition, to a lesser extent, the menstrual cycle could also influence the effect of exercise on arterial stiffness among middle-aged women [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has shown that endurance training positively affects arterial stiffness [57]. On the other hand, studies have shown no changes in arterial stiffness after resistance exercise [58][59][60]. HIIT studies may positively affect arterial stiffness [61,62]; however, this is controversial [63].…”
Section: Discussionmentioning
confidence: 99%
“…In healthy young people, traditional strength training (TRE) at intensities ≥ 60% 1RM induces an acute increase in arterial stiffness that is reflected by an augmentation of the pulse-wave velocity (PWV) [ 7 , 8 , 9 , 10 ]. An increase in arterial stiffness is thought to be a result of metaboreflex activation and higher sympathetic activity that causes a rise in blood pressure [ 11 ] and an elevated endothelin-1 concentration, leading to vasoconstriction [ 12 ].…”
Section: Introductionmentioning
confidence: 99%